2015
DOI: 10.1016/j.yebeh.2015.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Children with new onset seizures: A prospective study of parent variables, child behavior problems, and seizure occurrence

Abstract: Objective Parent variables (stigma, mood, unmet needs for information and support, and worry) are associated with behavioral difficulties in children with seizures, however, it is not known how this relationship is influenced by additional seizures. This study followed children (ages 4 – 14 years) and their parents over a 24-month period (with data collected at baseline, 6, 12, and 24 months) and investigated the effect of an additional seizure on the relationship between parenting variables and child behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Regardless of the aetiology, tubulointerstitium is a common target of injury during AKI, and multiple factors are involved in AKI‐to‐CKD progression. Sustained tubulointerstitial damage due to interstitial immune cell infiltration or tubular hypoxia induced by reduced peritubular capillary density, and subsequent interstitial fibrosis after AKI leads to glomerulotubular disruption and ultimate formation of atubular glomeruli, which develops into chronic renal dysfunction . Thus, urinary tubular markers during the chronic phase after AKI may reflect the degree of chronic tubulointerstitial damage after AKI and may be useful for monitoring AKI‐to‐CKD progression.…”
mentioning
confidence: 99%
“…Regardless of the aetiology, tubulointerstitium is a common target of injury during AKI, and multiple factors are involved in AKI‐to‐CKD progression. Sustained tubulointerstitial damage due to interstitial immune cell infiltration or tubular hypoxia induced by reduced peritubular capillary density, and subsequent interstitial fibrosis after AKI leads to glomerulotubular disruption and ultimate formation of atubular glomeruli, which develops into chronic renal dysfunction . Thus, urinary tubular markers during the chronic phase after AKI may reflect the degree of chronic tubulointerstitial damage after AKI and may be useful for monitoring AKI‐to‐CKD progression.…”
mentioning
confidence: 99%
“…35 Prior research has found lower levels of parent adaptive coping and more negative parent emotional response to seizures (eg, sadness or anxiety) to be associated with higher levels of parent-reported internalizing and externalizing problems in YWE. [36][37][38] YWE's health beliefs are also shaped by parent health beliefs and behaviors. For instance, perceived stigma in YWE is strongly influenced by parent stigma coaching, a process by which parental concealment shapes YWE's conceptualization of epilepsy as a discrediting attribute that should be hidden.…”
Section: Family Members' Perceptions Impacting Self-stigma and Disclo...mentioning
confidence: 99%
“…However, the impact of epilepsy goes well beyond seizures, affecting not only the child, but the entire family system (Ronen et al, 2010). The hidden, episodic, and unpredictable nature and course of epilepsy represents a significant and permanent source of stress, threatening the stability of the family system (Austin et al, 2015; Ronen et al, 2010). In addition, the high frequency of comorbidities such as learning difficulties and behavioral or emotional problems (Austin et al, 2010; Fastenau et al, 2004), the stigmatizing nature of the condition, and the potential for injury and death can curtail the social and leisure activities of the families and ultimately negatively affect children’s and their parents’ functioning across educational, emotional, social, and physical domains (Austin, Perkins, & Dunn, 2014; Painter, Rausch, & Modi, 2014).…”
mentioning
confidence: 99%